2018
DOI: 10.1002/srin.201700529
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Microstructure Characteristics and Enhanced Mechanical Properties of Spray Formed GCr15 Bearing Steel

Abstract: Bearing steel GCr15 is prepared by spray forming, and then goes through hot forging and heat treatment. Compared with conventionally cast material, microstructure characteristics and transformation mechanism of spray formed GCr15 bearing steel during each process are analyzed, and the final mechanical properties including strength, elongation, impact toughness, and wear resistance are tested. The results show that the microstructure of assprayed GCr15 bearing steel is homogeneous with very fine pearlite which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The researches show that proper heat treatment can optimize the microstructure of GCr15 and improve the strengthening effect of surface treatment on the surface properties of GCr15 [25][26][27][28][29]. Hao Su et al [30] investigated the surface ultrasonic burnishing treatment of TC11 titanium alloy and found that the heating surface of TC11 titanium alloy has better ultrasonic burnishing treatment results, significantly higher corrosion resistance, lower surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…The researches show that proper heat treatment can optimize the microstructure of GCr15 and improve the strengthening effect of surface treatment on the surface properties of GCr15 [25][26][27][28][29]. Hao Su et al [30] investigated the surface ultrasonic burnishing treatment of TC11 titanium alloy and found that the heating surface of TC11 titanium alloy has better ultrasonic burnishing treatment results, significantly higher corrosion resistance, lower surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Carbide distribution in hot-rolled rod reveals in the form of network and banded carbides, which are respectively precipitated proeutectoid carbide with band and reticulation form along austenite grain boundary with GCr15 hypereutectoid steel during the cooling process after rolling [12]. For GCr15 bearing steel, carbon segregation usually occurs in bloom continuous casting due to high carbon-chromium contents and long solidification time, which is the fundamental cause of forming carbide network and band during subsequent hot working process [13]. Hence, it is of vital importance in the improvement of carbide distribution in hot-rolled rod by improving carbon segregation of as-cast bearing steel.…”
Section: Introductionmentioning
confidence: 99%
“…Figure13. Variation of the measured values of average SDAS from surface to centre in cross-section of bloom for case1, case 2 and case 3.…”
mentioning
confidence: 99%